Development of In Situ Microfluidic System for Preparation of Controlled Porous Microsphere for Tissue Engineering - Ji Hwan Han; Chul Min Kim; Tae-Hyun Kim; Songwan Jin; Gyu Man Kim (MDPI AG, 2022)
In this study, we present an in situ microfluidic system to precisely control highly porous polycaprolactone microspheres as tissue templates for tissue engineering. The porosity of the microspheres was controlled by adjusting the flow rates of the polymer phase and the pore-generating material phase in the dispersed phase. The microfluidic flow-focusing technique was adopted to manufacture porous microspheres using a relatively highly viscous polymer solution, and the device was fabricated by conventional photolithography and PDMS casting. The fabricated in situ microfluidic system was used to precisely control the pore size of monodispersed polycaprolactone microspheres. The porous microspheres with controlled pore sizes were evaluated by culturing HDF cells on the surface of porous microspheres and injection into the subcutaneous tissue of rats. We found that the increased pore size of the microspheres improved the initial proliferation rate of HDF cells after seeding and relieved the inflammatory response after the implantation of porous microspheres in the subcutaneous tissue of rats.